Relationships of blood pressure with body mass index and total cholesterol among adults aged 19 or older, Bandar Lampung-Indonesia - Putri Agape Ramschie (Malahayati International Journal of Nursing and Health Science, 2025)
Background: High blood pressure, obesity, and elevated cholesterol are significant risk factors for cardiovascular diseases, making their interrelationship an important area of research. Purpose: To investigate the correlation between blood pressure, body mass index (BMI), and total cholesterol levels in adults residing. Method: Using a cross-sectional approach, data were collected from a sample of adults aged 25–60 years. Blood pressure was measured using a digital sphygmomanometer, BMI was calculated based on height and weight measurements, and total cholesterol levels were assessed through laboratory testing. Results: The findings indicate a positive correlation between BMI and blood pressure, suggesting that individuals with higher BMI are more likely to experience elevated blood pressure. Similarly, a significant relationship was observed between total cholesterol levels and both systolic and diastolic blood pressure. These results underscore the need for integrated health interventions targeting weight management and cholesterol control to reduce the risk of hypertension and associated health complications in the community. Conclusion: The study highlights the importance of routine health monitoring and lifestyle modifications in promoting cardiovascular health among adults.